2008
DOI: 10.1521/pedi.2008.22.5.466
|View full text |Cite
|
Sign up to set email alerts
|

Do Deficits in Mindfulness Underlie Borderline Personality Features and Core Difficulties?

Abstract: The current study investigated whether deficits in mindfulness (the awareness, attention, and acceptance of the present moment) can account for variability in borderline personality (BPD) features and characteristic difficulties in emotion regulation, interpersonal effectiveness, and impulsivity. Structural equation modeling and hierarchical regressions were utilized to examine the associations of trait mindfulness with BPD features, interpersonal problem-solving, impulsive and passive emotion-regulation strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
59
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 10 publications
9
59
0
3
Order By: Relevance
“…In addition, increased mindfulness predicts decreases in the reported use of dysregulated behaviors in attempts to modify emotions elicited by distressing situations (Wupperman, Neumann, & Axelrod, 2008;Wupperman, Neumann, Whitman, & Axelrod, 2009); this relationship is found in both clinical and community samples. Finally, mindfulness is inversely correlated with interpersonal conflict and negative emotions (Barnes, Brown, Krusemark, Campbell, & Rogge, 2007;Brown & Ryan), which are risk factors for a range of dysregulated behaviors (Anestis et al, 2010;Brown, Linehan, Comtois, Murray, & Chapman, 2009;Chen, Brown, Harned, & Linehan, 2009).…”
mentioning
confidence: 83%
“…In addition, increased mindfulness predicts decreases in the reported use of dysregulated behaviors in attempts to modify emotions elicited by distressing situations (Wupperman, Neumann, & Axelrod, 2008;Wupperman, Neumann, Whitman, & Axelrod, 2009); this relationship is found in both clinical and community samples. Finally, mindfulness is inversely correlated with interpersonal conflict and negative emotions (Barnes, Brown, Krusemark, Campbell, & Rogge, 2007;Brown & Ryan), which are risk factors for a range of dysregulated behaviors (Anestis et al, 2010;Brown, Linehan, Comtois, Murray, & Chapman, 2009;Chen, Brown, Harned, & Linehan, 2009).…”
mentioning
confidence: 83%
“…Wupperman et al (2008) found that in social problem-solving situations, a composite variable of passive and impulsive emotion regulation styles was negatively associated with mindfulness in a non-clinical population. However, no research to date has directly examined the relationship between selfreported mindfulness and trait-level impulsivity.…”
Section: Introductionmentioning
confidence: 89%
“…Evidence suggests that low abilities in mindfulness may account for BPD-specific problems in emotion regulation, interpersonal function, and impulsivity (e.g., Wupperman et al, 2008;Wupperman et al, 2009;Fossati et al, 2011). In a preliminary study examining the mediating effect of mindfulness on BPD symptoms, Wuppermann and colleagues (2013) suggested that typical dysregulated behaviors observed in BPD --for instance, self-injury, substance abuse, suicide attempts, or physical aggression (American Psychiatric Association, 2000) --were associated with a low level of mindfulness (Wupperman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%